The Relation Between Classroom Age Composition and Children's Language and Behavioral Outcomes: Examining Peer Effects. Issue 6 (22nd August 2020) - Foster, Tiffany J.; Burchinal, Margaret; Yazejian, Noreen
Abstract : Grouping children of different ages in the same preschool classroom (i.e., mixed age) is widespread, but the evidence supporting this practice is mixed. A factor that may play a role in the relation between classroom age composition and child outcomes is peer skill. This study used a sample of 6, 338 preschoolers (ages 3–5) to examine the influence of both classroom age composition and peer skill on children's behavioral and language outcomes. Results supported the growing literature indicating preschoolers' skills are higher when peer skill is higher, but differences related to classroom age composition were not found. These findings further support the view that peer skill plays an important role in preschool children's outcomes.